Ekstrak daun kedondong laut (Polyscias fruticosa) sebagai modulator imun benih ikan nila (Oreochromis niloticus) - Dahlia Malau; Reiny A. Tumbol; Sammy N. J. Longdong; Reni L. Kreckhoff; Winda M. Mingkid; Edwin L. A. Ngangi (Universitas Sam Ratulangi, 2023)
Disease control using medicinal plants is an alternative to antibiotics and chemicals in aquaculture. One type of plant with the potential for health management is Polyscias fruticosa or sea kedondong which contains flavonoids, saponins, methanol, and tannins that are efficacious as antihistamines, antioxidants, antivirals, antibacterials, anti-inflammatories, and anti-cancer. The aim of the study was to examine the effect of kedondong laut leaf extract on increasing the phagocytic activity of tilapia (Oreochromis niloticus), and to determine the appropriate concentration of kedondong laut leaf extract to increase the phagocytic activity of tilapia (O. niloticus) seeds. The leaves of kedondong laut are cleaned, washed, and dried for 14 days at room temperature and then ground using a blender to obtain an extract of coarse flour. The flour was extracted using the maceration method with 70% alcohol solvent with a ratio of coarse flour and the solvent 1:5. After 24 hours of soaking, the extract was filtered using Whatman paper No. 42, and the dregs were soaked again with the same volume of solvent for the same soaking time and filtered again. This process is done 3 times until the extract looks clear. The extract was then concentrated using a rotary evaporator to obtain a concentrated extract of about 30% of the initial total extract. The concentrated extract is then sprayed evenly using a sprayer into the feed according to the set treatment dose. The research design used was Completely Randomized with 5 treatments, each with 3 replications. The treatments used were A: 0%, B: 1%, C: 2%, D: 3%, and E: 4% extract/kg feed. Treatment feed was given for 4 weeks at a dose of 5%/body weight/day, and the frequency of feeding was 2 times a day at 08:00 and 16:00. The results showed that the administration of sea kedongong leaf extract had a very significant effect on the phagocytic activity of tilapia (p<0.01). The best results were achieved in fish treated with B (1% extract/kg) for 28 days. Keywords: medicinal plants, maceration, immune modulators, phagocytosis activity, disease control